2020
DOI: 10.1007/s00296-020-04526-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions in the treatment of rheumatoid arthritis and psoriatic arthritis

Abstract: Background Treating patients with inflammatory joint diseases (rheumatoid arthritis, psoriatic arthritis) according to established treatment algorithms often requires the simultaneous use of three or more medications to relieve symptoms and prevent long-term joint damage as well as disability. Objective To assess and give an overview on drug-drug interactions in the pharmacotherapy of inflammatory joint diseases with regards to their clinical relevance. Methods All possible drug combinations were evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
9
0
4
Order By: Relevance
“…The number of patients affected by polypharmacy considerably varies when using different definitions (3). Polypharmacy may result in unwanted drug interactions (4), and/or lead to an increase of adverse and serious adverse events, with more frequent admissions to hospitals, thus extending the costs of health care (5). In elderly people over 65 years, more than 50% are prescribed more than 6 medications, and almost 20% receive an inappropriate drug (5).…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients affected by polypharmacy considerably varies when using different definitions (3). Polypharmacy may result in unwanted drug interactions (4), and/or lead to an increase of adverse and serious adverse events, with more frequent admissions to hospitals, thus extending the costs of health care (5). In elderly people over 65 years, more than 50% are prescribed more than 6 medications, and almost 20% receive an inappropriate drug (5).…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy can lead to adverse drug interactions ( 83 ) and increase severe adverse events, thereby increasing healthcare costs ( 84 ). In elderly patients over 65 years of age, 50% will be prescribed more than 6 drugs, and nearly 20% will receive inappropriate medication ( 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…A change in pharmacokinetics and pharmacodynamics occurs during sepsis [29] and studies have shown a relatively high frequency of pDDIs in patients with sepsis treated in ICU [30]. Also, the patients with autoimmune disease were significantly exposed to pDDIs [31].…”
Section: Discussionmentioning
confidence: 99%